A new Bernard–Praly-like observer for sensorless IPMSMs. (June 2022) - Verrelli, Cristiano Maria; Carfagna, Emilio; Frigieri, Matteo; Crinto, Andrea Stefano; Lorenzani, Emilio
Abstract: A slight extension of the global Bernard–Praly gradient adaptive observer – originally presented for nonsalient-pole surface Permanent Magnet Synchronous Motors (PMSMs) and recently proved to own local exponential convergence properties under well-known observability conditions – is here designed and proposed for Interior Permanent Magnet Synchronous Motors (IPMSMs) (with relatively small saliency) in the case in which the q -axis current is constant. It guarantees local exponential estimation – from stator current and voltage measurements – of both the stator fluxes and the sinusoidal/co-sinusoidal functions of the motor electrical angle, with no modification of the previous persistency of excitation condition requirements. Such an extension complements – at least locally – a previous analysis concerning IPMSMs under constant d -axis current. Applications to the sensorless control of IPMSMs (with realistic simulations) are included.